Perspectives de reconversion pour les moulins des Alpes Apuanes - Boissenin, Lucie (Scienze del Territorio, 2018)
This article presents a study made during the summer 2016 at the University of Florence. It took place within a larger research project entitled “Comparative study of inland areas for the territorial planning in the energy sector through pilot projects for local development”, in which different areas were analysed, among them the Apuan Alps in northern Tuscany. The main goal of the research was to evaluate the opportunities for a more sustainable development of the energy sector in inland area. In the Apuan Alps, two main energy resources – biomass and water – have been identified. Our study mainly concerned the second one and, in particular, the chance to transform the surviving mills into pico- or micro-hydroelectric power stations. This could pave the way to a more ‘territorialised’ energy production and, at the same time, guarantee the protection of an architectural heritage which is an expression of local identity.